How domestic anti-avoidance rules affect double taxation conventions : proceedings of a seminar held in Toronto in 1994 during the 48th Congress of the International Fiscal Association /: proceedings of a seminar held in Toronto in 1994 during the 48th Congress of the International Fiscal Association. (2016) - Unknown
No abstract available